2015
DOI: 10.1155/2015/581785
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Nanoparticles for Enhancing Carbon Capture

Abstract: Hydration reaction of CO2is one of the rate limiting steps for CO2absorption (in aqueous solutions) and aqueous CO2mineralization. The catalytic activity of nickel nanoparticles (NiNPs) for CO2hydration is studied at different temperatures, pH, and low CO2partial pressures to mimic the true flue gas conditions. Results show that NiNPs can work as active catalyst for hydration of CO2in applications such as CO2separation and CO2mineralization. The NiNPs display optimum activity within 20–30°C and at pH value <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…There was no significant difference in the exhibited elements according to the setting time (3, 6 and 12 min and 24 h groups). The XRD spectra exhibited peaks for calcium carbonate [ 57 ], zirconium oxide [ 58 ], and calcium hydroxide [ 47 , 59 ]. In the 24 h group, the peak for calcium hydroxide was relevantly lower than those in the during setting groups, and the surface was not deposited with microstructural particles, unlike the surfaces of the during setting groups.…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in the exhibited elements according to the setting time (3, 6 and 12 min and 24 h groups). The XRD spectra exhibited peaks for calcium carbonate [ 57 ], zirconium oxide [ 58 ], and calcium hydroxide [ 47 , 59 ]. In the 24 h group, the peak for calcium hydroxide was relevantly lower than those in the during setting groups, and the surface was not deposited with microstructural particles, unlike the surfaces of the during setting groups.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles are further developed as catalyst to solve the rapid reaction of HCl and CO 2 gas production in matrix acidizing for carbonate reservoir (Raj and Pal 2014). The proposed research has used nickel nanoparticles to accelerate the conversion of in situ organic acid from CO 2 gas, which reduces the need of expensive well tubulars and organic retarders (Ogolo et al 2012;Bhaduri et al 2015). Throughout the acidizing job, the nanoparticles…”
Section: Nanoparticles In Catalytic Reactionmentioning
confidence: 99%
“…Faridi et al ( 2017 ) showed that even after 22 cycles of reuse, recombinant α–CA (rBhCA) from B. halodurans TSLV1 immobilized on silanized iron MNPs (rBhCA-Si-MNPs) lost only 50% of activity. Nickel nanoparticles have been successfully used as a direct catalyst for CO 2 hydration reaction for assessing their application in CO 2 mineralization (Bhaduri et al, 2015 ).…”
Section: Carbon Capture and Storage (Ccs)mentioning
confidence: 99%